(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the benefits of hybrid modality to the Grade 11 Humanities and Social Sciences (HUMSS) students at Bestlink College of the Philippines in terms of their learning, communication, financial support, time management, adaptation of hybrid systems, and resource availability. The survey’s results, along with other study-related aspects, showed that using a hybrid modality boosted students’ academic performance. A majority of survey respondents strongly agree that applying a hybrid learning approach benefits them because it allows them to use technological advances as a learning tool with greater efficiency, increases their learning, and fosters accountability. When engaging in face-to-face classes in the hybrid modality, they can easily communicate with their instructors and classmates. However, adjusting to the hybrid modality of learning enables students to learn in more effective ways. The majority of respondents who responded strongly agreed that using the LMS gives them better access to information and, therefore, helps improve their comprehension of their classes. This study recommended that the students ought to be encouraged to develop more confidence in participation and learn how to interact with or adjust to the system in a hybrid modality. It is further urged that the hybrid learning modality’s grading system be improved in the future so that students can utilize it as a driving force.